Sexual dimorphism of mandibular measures from computed tomographies - Renato Taqueo Placeres ISHIGAME; Alicia PICAPEDRA; Carlos SASSI; Viviane ULBRICHT; Vanessa Gallego Arias PECORARI; Francisco HAITER NETO; Eduardo DARUGE JÚNIOR; Luiz FRANCESQUINI JÚNIOR (Faculdade São Leopoldo Mandic, 2019)
Objetive: The objective of this study was to analyze mandibular measurements obtained from 225 computed tomography scans of the Osteological and CT Biobanks of Faculdade de Odontologia de Piracicaba Universidade Estadual de Campinas, aiming to verify the existence of a relationship between these measures and sexual dimorphism and ancestry. METHODS: We sought to establish a mathematical model capable of estimating sex and ancestry. Of these scans, 126 were male, 94 were female and 5 were unidentified, aged 15 to 100 years, and ancestry known for the skin color phenotype (white, black, brown and yellow). Measurements were made between the following points: right lateral condylion and left lateral condylion; right lateral condylion and pogonion; left lateral condylion and pogonion; mesial border of right mental foramen and mesial border of left mental foramen. The area delimited by the triangle formed by the measurements between right lateral condylion and left lateral condylion was also analyzed; right lateral condylion and pogonion; and left lateral condylion and pogonion. Student t test for homogeneous variances showed that there was statistical difference in the means as a function of sex, except for the area measure, which was not used in the model. RESULTS: It was possible to establish a mathematical model with accuracy of 69.2%. There was no statistical difference in the averages as a function of ancestry. ONCLUSION: It is concluded that the measures investigated help in the process of estimating sex, but were not adequate to estimate ancestry. The proposed methodology should be expanded to other population groups so that it can be improved.